RELIGIOUS STUDIES AND THE TEACHING OF BUSINESS ETHICS - Muldoon, Maureen (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 1990)
The field of business ethics is in the process of defining its goals, developing its methods, and determining its constituent disciplines. Currently, business ethics courses are offered through religious studies departments, but there are those who strongly advocate that business ethics be taught in business schools, primarily by business people. This article discusses the contributions and limits of a religious studies perspective for business ethics. RÉSUMÉ On s'emploie actuellement à définir les objectifs et les méthodes de l'éthique commerciale, et à cerner les disciplines qui la constituent. Des cours d'éthique commerciale sont actuellement dispensés par les départements d'études religieuses, mais certains recommandent vivement que ces cours relèvent des écoles d'administration et soient donnés surtout par des hommes/femmes d'affaires. L'auteur analyse l'apport et les limites de la perspective religieuse, appliquée à l'éthique commerciale.